Greenland, stream and valley at Kjerulf Fjord - Boyd, Louise Arner, 1887-1972 (1931)
August 1, 1931. Kjerulfs [Kjerulf] Fjord. Extreme inner end. In background on left southern terminal of mountains forming eastern side of Kjerulfs [Kjerulf] Fjord. Here they are seen forming east side of Left Valley. Mountains in background are those forming eastern side of Hisinger Glacier [Hisinger Gletscher] after glacier has turned south at L.A.B.'s Scoop Mt. [Mountain] On right, stream of Left Valley from source near glacier to mouth, where it is shown joining waters from Right Valley, which are in foreground at bottom of photo. Photo taken from floor of Main Valley at junction Right and Left Valley, looking S.S.E.